2022
DOI: 10.2967/jnumed.121.263318
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating Glioma-Associated Microglia and Macrophage Dynamics Under CSF-1R Therapy with Multitracer In Vivo PET/MRI

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…TSPO is not only expressed in myeloid cells of the tumor microenvironment (TME) but also in tumor cells in dependence of the glioma grade ( 1 ). Despite the expression by various cell types, TSPO could serve as a potential imaging biomarker to characterize the immunosuppressive phenotype of glioblastoma during immunomodulatory treatment ( 2 ). Furthermore, due to the assumed strong elevation of TSPO in the infiltration zone ( 1 ), this biomarker may have potential to identify brain regions that are subject to tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSPO is not only expressed in myeloid cells of the tumor microenvironment (TME) but also in tumor cells in dependence of the glioma grade ( 1 ). Despite the expression by various cell types, TSPO could serve as a potential imaging biomarker to characterize the immunosuppressive phenotype of glioblastoma during immunomodulatory treatment ( 2 ). Furthermore, due to the assumed strong elevation of TSPO in the infiltration zone ( 1 ), this biomarker may have potential to identify brain regions that are subject to tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The value of TSPO imaging in glioma was already determined in prognostication and detection of tumor heterogeneity ( 5 , 6 ). For back translation and mechanistic elucidation of observations in humans as well as for TSPO biomarker monitoring during experimental testing of therapeutics, animal models provide a tremendous value across brain diseases ( 2 , 7 , 8 ). First experimental glioblastoma investigations with murine GL261 in immunocompetent mice ( 9 ), human P3 in immunodeficient mice ( 10 ), and human U87 in immunodeficient rats ( 11 ) indicated feasibility of TSPO PET monitoring by different radiotracers.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the inhibition of activated microglia reduced pathological angiogenesis in the early stage and then rescued the over-apoptosis of photoreceptors. Moreover, the therapy of PLX5622-mediated modulation of GAMM might be a novel therapy against glioma [ 50 ]. Therefore, local inhibition of microglia activation has considerable therapeutic prospects in ocular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The second-and third-generation tracers have shown superior imaging properties, while they are not yet fully characterized [34]. The use of TSPO PET tracers has been corroborated in several glioma models and showed to (i) improve tumor and immune cell detection, (ii) provide complementary information to [ 18 F]FET PET and MR imaging, (iii) be a suitable biomarker for glioma growth and immune cell infiltration, and (iv) define glioma heterogeneity in combination with other imaging modalities [33,[35][36][37][38][39]. In patients with positive uptake for both tracers, the mean percentage of overlap was 24.56%.…”
Section: Translocator Protein (Tspo) Pet Imagingmentioning
confidence: 99%
“…The authors observed that [ 18 F]DPA-714 PET VOI was not significantly changed with GAMs depletion while the progression of glioma-associated inflammation was slowed down following inhibitor withdrawal. Subsequently, Foray et al employed a colony-stimulating factor 1 receptor (CSF-1R) inhibitor to efficiently deplete GAMs within the TME in an orthotopic syngeneic GL261 mouse model and assessed therapy response using [ 18 F]FET and [ 18 F]DPA-714 PET imaging at days 7, 14 and 21 post-injection (Figure 4) [37]. The authors observed that [ 18 F]DPA-714 PET VOI was not significantly changed with GAMs depletion while the progression of glioma-associated inflammation was slowed down following inhibitor withdrawal.…”
Section: Therapy Readoutmentioning
confidence: 99%